Barley fibre and wet distillers’ solubles in the diet of growing cattle - Root, Tarja; Huhtanen, Pekka (Agricultural and Food Science, 1998)
Twenty-eight bulls were used in a 3 x 2 factorial design to study the effects of two by-products from the integrated starch-ethanol process, barley fibre and distillers’ solubles, as supplements for grass silage. The animals were divided into five blocks and slaughtered when the average live weight (LW) of each block reached 500 kg. The three energy supplements were barley (B), a mixture (1:1 on a dry matter (DM) basis) of barley and barley fibre (BF), and barley fibre (F), fed without (DS-) or with (DS+) wet distillers’ solubles (200 g kg-1 concentrate on DM basis). Concentrates were given at the rate of 95 g DM kg-1 LW0.6. Including barley fibre in the diet did not affect feed intake, but distillers’ solubles tended to increase both silage and total DM intakes as well as amino acids absorbed in the intestine and energy intake. The protein balance in the rumen increased with the inclusion of barley fibre (P<0.001) and distillers’ solubles in the diet (P<0.01). Even though barley fibre had lower energy content than barley, it did not affect metabolizable energy (ME) intake markedly. The average daily LW gain of all groups was high, and it was not significantly different for the various supplements. However, towards the end of the experiment the LW gain of bulls fed with barley fibre tended to decrease compared to barley. Feed conversion rates in terms of kg DM and MJ ME kg-1 LW gain and the carcass weight or quality were not significantly affected by the treatments.